2017
DOI: 10.2334/josnusd.16-0295
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> study of antifungal effects of low-molecular-weight chitosan against <i>Candida albicans </i>

Abstract: This study investigated the antifungal effects of low-molecular-weight chitosan solution onCandida albicans in denture stomatitis in comparison with nystatin suspension. This randomized, singleblind clinical trial included 40 patients diagnosed with denture stomatitis. Patients were divided into two groups, wherein one was treated with chitosan and the other with nystatin for 2 weeks. Changes in the erythematous area were recorded during and after treatment. A palatal smear was obtained for each patient before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…Furthermore, the high molecular weight of CS decreases the hydrophobicity and adhesion of C. albicans to epithelial and human fibroblast cells [33] and the adhesion to dentures [34]. Furthermore, an in vivo study showed promising results for the use of low-molecular weight (LMW) CS solution for the treatment of DS [35]. Therapy with CS solution decreased the erythematous surface area, burning sensation, the time required for clinical improvement, and the number of blastospores and mycelia [35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high molecular weight of CS decreases the hydrophobicity and adhesion of C. albicans to epithelial and human fibroblast cells [33] and the adhesion to dentures [34]. Furthermore, an in vivo study showed promising results for the use of low-molecular weight (LMW) CS solution for the treatment of DS [35]. Therapy with CS solution decreased the erythematous surface area, burning sensation, the time required for clinical improvement, and the number of blastospores and mycelia [35].…”
Section: Introductionmentioning
confidence: 99%
“…According to Mishra et al [13] there was a significant reduction on biofilm formation and biomechanical characteristics of dental cements when chitosan was used in the mixture, as well as a better compressive strength with P < 0.001 statistical value. Atai et al [14] reported no significant results on clinical signs to prevent mycosis ( P > 0.05). Mandrazo-Jimenez et al [15] reported no significant differences between swelling, pain, and wound healing after oral surgery maneuvers.…”
Section: Resultsmentioning
confidence: 99%
“…This type of modified cement has improved physical properties as compared to a chitosan modified cement or a conventional cement. According to Atai et al [14] chitosan is a valid alternative because it is antifungal, and with its biocompatibility it is a candidate for antifungal mouthwash. Mandrazo-Jimenez et al [15] evaluated the effects of a topical gel containing chitosan, 0,2% chlorhexidine allantoin, and dexpanthenol on wound healing [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a simple linear polysaccharide that constitutes the β-1-4 linked D-11 glucosamine (GlcN) and N-acetyl-D-glucosamine (GlcNAc) (Katiyar, Hemantaranjan, Singh, & Bhanu, 2014). Chitosan is known to induce plant growths (Dzung, Khanh, & Dzung, 2011), contain antifungal (Atai, Atai, Amini, & Salehi, 2017;Dananjaya et al, 2017) and antibacterial properties (Cui, Bai, Rashed, & Lin, 2018;D'Almeida et al, 2017). Investigation on the role of nano-chitosan against pathogens have been reported in rice (Pham et al, 2019) and tomato (Chun & Chandrasekaran, 2019;Santiago et al, 2019).…”
Section: Introductionmentioning
confidence: 99%